Association between type 2 inflammatory diseases and neurodevelopmental disorders in low-birth-weight children and adolescents - Huang, Hengye; Zhang, Kelvin Pengyuan; Sun, Karol Kexin; Yu, Guangjun (Frontiers in Psychology, 2024)
Background Evidence of the association of certain neurodevelopmental disorder with specific type 2 inflammatory (T2) disease has been found. However, the association of various neurodevelopmental disorders with T2 diseases as a whole remains unclear in low birth weight (LBW) infants. Objective To evaluate the association of type 2 inflammatory (T2) diseases with intellectual disability (ID), autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), and learning disability (LD) in low-birth-weight (LBW) children and adolescents. Methods The study sample was derived from 2005-2018 National Health Interview Survey sample child files. LBW children and adolescents aged 3–17 were included. History of T2 diseases (including asthma and atopic dermatitis) and four neurodevelopmental disorders were reported by adults in families. The relationship between T2 diseases and the risk of four neurodevelopmental disorders was investigated through multiple-weighted logistic regression. Age, sex, race/ethnicity, region, highest education in family and ratio of family income to the poverty threshold were adjusted as covariates for model estimation. Subgroup analyses were conducted by age stratification (3-11 years and 12-17 years), sex (male and female), and race (white and non-white). Results 11260 LBW children aged 3–17 years (mean age [SE], 9.73 [0.05] years) were included, in which 3191 children had T2 diseases. History of T2 diseases was associated with an increased risk of neurodevelopmental disorders, with an OR of 1.35 (95% CI, 0.99–1.84) for ID, 1.47 (95% CI, 1.05–2.05) for ASD, 1.81 (95% CI, 1.51–2.16) for ADHD, and 1.74 (95% CI, 1.49–2.04) for LD following the adjustment of all the covariates. The correlations between T2 disorders and each of the four neurodevelopmental disorders were significantly different by sex and race (all P for interaction < 0.001), and no differences were found in age stratification (all P for interaction > 0.05). Conclusion In a nationally representative sample of children, we found a significant association of T2 diseases with ASD, ADHD, and LD, even after adjusting for demographic baseline. We also found that the association of T2 disease with neurodevelopmental disorders differed between sex and race. Further investigation is needed to evaluate causal relationships and elucidate their potential mechanisms.